PERANCANGAN BACKDROP SMA NEGERI 1 GIRIMULYO DENGAN MOTIF BATIK GEBLEK RENTENG SEBAGAI REPRESENTASI BUDAYA KULON PROGO DAN EDUKASI SISWA - wicaksono, Noor Fatih Ario; Muryasari, Desiana (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2025)
The Geblek Renteng batik motif is a distinctive cultural heritage from the Kulon Progo region of Yogyakarta. This motif is inspired by the traditional food ‘geblek,’ which is served in a lined arrangement, and it reflects the philosophy of togetherness, simplicity, and a deep local identity. Furthermore, this motif serves as a symbol of local wisdom and holds significant potential for development within the creative industry. This study aims to explore the additional potential of applying the Geblek Renteng motif as a decorative element in interior design, specifically in backdrop design. The chosen design object is SMAN 1 Girimulyo, located in Kulon Progo, the birthplace of the motif. The use of the Geblek Renteng motif as a decorative element is expected to serve as an educational tool for students regarding the importance of preserving local culture amidst the increasingly strong currents of globalization.